Early recognition and detection of juvenile psoriatic arthritis: a call for a standardized approach to screening - Burden-Teh, Esther; Thomas, K.S.; Rangaraj, S.; Cranwell, J.C.; Murphy, R. (Wiley, 2017)
Background: National Institute for Health and Care Excellence (NICE) guidelines recommend annual screening for psoriatic arthritis (PsA) in all patients with psoriasis. Currently, no validated assessment tools have been recommended for screening for juvenile PsA (JPsA).